Structural heterogeneity of dengue virus particles: implications for vaccine design - Keelapang, Poonsook; Sittisombut, Nopporn (Biomedical Sciences and Clinical Medicine, 2024)
Dengue virus infection continues to pose serious public health threat in tropical regions around the world. Existing countermeasures against mosquito vectors of dengue viruses are limited and largely ineffective in the long term basis. A tetravalent live, attenuated vaccine candidate is currently tested in phase III clinical trial. Additional candidates in various forms are being generated with a common goal of obtaining safe, effi cacious and accessible dengue vaccine for general use. Recent studies on the structure of dengue virus particles and specifi c immunological responses induced during natural infection reveal a complex mixture of extracellular virus particles at different maturation levels that may play an essential role the generation of predominantly crossreactive B cell responses in infected individuals. Applications of these fi ndings in the design of newer vaccine candidates will be crucial to the development of effective dengue vaccine in the future.